A violação de Britânico (Tac. Ann. 13.17) = Britannicus’ Rape (Tac. Ann. 13.17) - Simões Rodrigues, Nuno (Espacio Tiempo y Forma. Serie II, Historia Antigua, 2020)
Este estudo foca-se na biografia de Britânico, filho de Cláudio e Valéria Messalina, analisando em particular as informações transmitidas por Tácito nos Annales. Esta obra é também a única fonte que dá conta de que Britânico teria sido sexualmente violado por Nero, seu irmão por adoptio, cunhado e concorrente ao poder. Pretendemos, assim, analisar também a referência ao stuprum do jovem príncipe e o seu significado na historiografia de Tácito. Abstract This essay focuses on the biography of Britannicus, son of Claudius and Valeria Messalina, considering particularly the information transmitted by Tacitus in the Annales. Tacitus’ work is also the only source that realizes that Britannicus would have been sexually assaulted by Nero, his brother by adoption, brother-in-law and rival as far as power was concerned. Thus, we also intend to analyse the reference to the stuprum of the young prince and its meaning within the historiography of Tacitus.